Distributions of Ni and Fe in the different tissues of snail Faunus ater and bivalve Psammotaea elongata - Yap, Chee Kong; Yaacob, Aziran; Ismail, Mohamad Saupi; Wan Mohd Syazwan, .; Okamura, Hideo; Horie, Yoshifumi; Ong, Meng Chuan; Setyawan, Ahmad Dwi; Kumar, Krishnan; Cheng, Wan Hee; Nulit, Rosimah; Yap, Chee Wah (MedCrave Group, 2023)
Gastropods Faunus ater and bivalves Psammotaea elongata were sampled from the intertidal waters of Pantai Sri Tujuh, Tumpat (Kelantan), and their different soft tissues and shells were determined for Ni and Fe. The outcomes showed that the shells of the two species had significantly (P< 0.05) higher non-essential Ni levels than those in the different soft tissues. The contrary results were found in the essential Fe, where different soft tissues had significantly (P< 0.05) higher Fe concentrations than those in the shells of the two molluscs. This phenomenon could be due to the different essentiality of the two different groups of Ni and Fes between the different soft tissues and shells of molluscs. The present f inding indicated the shells of P. elongata and F. ater were storage sites for Ni.